Identification Of The Hierarchy Of Ecotourism Criteria Using The AHP Method: Reference For Determining Priority Villages For Ecotourism Development - Prasandya, Km. Deddy Endra; Satria, Made Wina (Politeknik Internasional Bali, 2023)
The existence of government programs that change the direction of tourism development from mass tourism which is considered to cause degradation of environmental, socio-economic and cultural aspects, to quality tourism, is also a concern for Bali tourism leaders to participate in efforts to change the direction of Bali tourism development through the development of ecotourism. The proof is that many studies/research have been conducted to add new forms of more sustainable tourist destinations in Bali. The study concluded that many villages in Bali have the potential to be developed as ecotourism. The focus of this research is to formulate a hierarchy of criteria for ecotourism development using the AHP (Analytical Hierarchy Process) method. The hierarchy of ecotourism development criteria can be used as an indicator to assess the next ecotourism priority village. This research is a mixed method research, where identification and weighting will be carried out through the Decision Support System (SPPK) with the AHP method. Secondary data collection in the form of research that has been carried out previously and supporting literature related to ecotourism is used to formulate criteria and sub-criteria for ecotourism development. This formulation is used as initial information in the process of weighing ecotourism criteria and sub-criteria. The results showed that there are six ecotourism criteria that can be used in determining priority villages for future ecotourism development including environmental criteria (absolutely more important: 0.281), socio-cultural (0.210), level of community participation (0.168), education (0.166), economy (0.100), and institutional (0.075).